Resin microparticles and resin microparticle-containing composition
Fine resin particles with a defined absorbance ratio in the infrared spectrum address the issues of detachment and scratch resistance in films, ensuring adhesion and durability through a simple production method.
Patent Information
- Application Number
- JP2021030954
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Filing Date
- 2021-02-26
- Publication Date
- 2025-01-22
- Estimated Expiration
- 2041-02-26
AI Technical Summary
Existing resin fine particles used in films for optical and electronic devices face issues such as falling off from the base material or binder, lack of scratch resistance, and complex production methods, which affect their performance and durability.
The development of fine resin particles with a specific absorbance ratio in the infrared spectroscopic spectrum, produced by polymerizing vinyl monomers, including polyfunctional vinyl monomers, to enhance adhesion and scratch resistance, using a simple method.
The resin particles effectively prevent detachment from the base material, provide scratch resistance, and maintain transparency, while being produced through a straightforward process.
Smart Images

Figure 0007618919000001
Abstract
Description
[Technical field]
[0001] The present invention relates to fine resin particles obtained by polymerizing a vinyl monomer and a composition containing fine resin particles. [Background technology]
[0002] The applications of resin microparticles have continued to expand in recent years, and they are used in a wide range of applications, such as additives for resin films, spacers between minute parts of various electronic devices, pore-forming agents for various battery components, and core particles of conductive microparticles that provide electrical connections. Among these, examples of additives for resin films include additives for resin films used in optical components such as light diffusion films and antiglare films, and electronic device applications, antiblocking agents for various resin films, and modifiers for various resin films.
[0003] Resin films used for optical components and electronic devices are required to have increasingly sophisticated properties. Representative properties include anti-sticking, high transparency, high durability, scratch resistance, etc. These properties are imparted to the base film directly or in a post-process such as coating. Among these properties, anti-sticking property is an important property for preventing the resin films from sticking to each other at overlapping portions when the resin films are stored in a rolled state, and for preventing deterioration of the slipperiness and peelability of the resin films. To address the issue of imparting anti-sticking property to the resin film, it is known to add resin fine particles or inorganic particles as an anti-sticking agent.
[0004] Examples of the anti-sticking agent include inorganic particles such as silica, and resin particles such as (meth)acrylic resin particles. The advantage of silica is its high hardness, and adding a small amount can provide anti-sticking properties. However, due to its material properties, there is a disadvantage that a refractive index difference occurs between the material and the resin film, which can cause a loss of transparency. On the other hand, resin microparticles have the advantage that they can be used in resin films that require high quality because they maintain the transparency of the resin film and can impart anti-sticking properties. However, they are inferior in strength to inorganic particles.
[0005] Patent Document 1 describes crosslinked resin fine particles obtained by using a technique for improving strength by improving the crosslinked structure. Patent Document 2 describes the application of core-shell type lubricating particles to an optical film to impart anti-sticking properties while maintaining transparency. Patent Document 3 describes that the affinity with a matrix resin is improved by using resin fine particles having at least one reactive functional group selected from a hydroxyl group, an epoxy group, a carboxyl group, and an alkoxysilyl group, and an ethylenically unsaturated group. [Prior art documents] [Patent documents]
[0006] [Patent Document 1] Patent No. 6258740 [Patent Document 2] JP 2017-181990 A [Patent Document 3] Patent No. 5011731 Summary of the Invention [Problem to be solved by the invention]
[0007] However, while the crosslinked fine particles described in Patent Document 1 can provide transparency and anti-sticking performance when made into a film, problems remain in terms of scratch resistance, etc., because particles fall off from the substrate or binder. Similarly, the core-shell particles described in Patent Document 2 also fail to provide scratch resistance, because particles fall off. In addition, the reactive monodisperse resin fine particles described in Patent Document 3 can provide scratch resistance, but the method for producing the particles is complicated, and problems remain in terms of production and cost.
[0008] An object of the present invention is to provide resin microparticles and a composition containing resin microparticles, which are prepared by a simple method, and which are capable of preventing the resin microparticles from falling off a substrate or a binder and imparting scratch resistance to a film. [Means for solving the problem]
[0009] The present inventors conducted intensive research in light of the above-mentioned problems and discovered that, while the resin microparticles are produced by a simple method, by setting the absorbance ratio of the maximum absorbance in a specific wavenumber range in the infrared spectrum to a specific range, it is possible to produce resin microparticles that can prevent the resin microparticles from falling off from the substrate or binder and can impart scratch resistance to the film. Specifically, the present invention is as follows. [1] Obtained by polymerizing one or more vinyl monomers, In the infrared spectrum measured by the ATR method using an infrared spectrophotometer, the wave number was 1700 cm -1 ~1800cm -1 Maximum peak height (maximum absorbance) (A) and wavenumber 1600 cm -1 ~1700cm -1 The absorbance ratio (B) / (A) of the maximum peak height (maximum absorbance) (B) is in the range of 0.020 to 0.060. [2] The resin microparticles according to [1], wherein the vinyl monomer includes a polyfunctional vinyl monomer. [3] The resin microparticles according to [1] or [2], wherein the vinyl monomer comprises a (meth)acrylic acid ester monomer. [4] The resin fine particles according to any one of [1] to [3], wherein the content of the polyfunctional vinyl monomer is in the range of 51 parts by mass to 100 parts by mass per 100 parts by mass of the vinyl monomer. [5] The fine resin particles according to any one of [1] to [4], wherein the amount of unreacted vinyl monomer in the fine resin particles is 1.0 mass % or less. [6] The resin fine particles according to any one of [1] to [5], which are a dry powder having a moisture content of 2.0 mass % or less. [7] A resin microparticle-containing composition comprising the resin microparticles according to any one of [1] to [6], a photopolymerization initiator, and an ultraviolet-curable resin. Effect of the Invention
[0010] The resin microparticles of the present invention are resin microparticles that can be produced by a simple method, yet can be prevented from falling off a substrate or a binder, and can provide a resin microparticle and a resin microparticle-containing composition that can impart scratch resistance to a film. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0011] The resin fine particles and the resin fine particle-containing composition of the present invention will be described in detail below. In this specification, the (meth)acrylic acid ester monomer means an acrylic acid ester monomer or a methacrylic acid ester monomer, and the (meth)acrylic acid means acrylic acid or methacrylic acid.
[0012] [Resin fine particles] The resin microparticles of the present invention are obtained by polymerizing one or more vinyl monomers, such as one or more selected from monofunctional vinyl monomers having one or more vinyl groups in one molecule and polyfunctional vinyl monomers having two or more vinyl groups in one molecule.
[0013] <Monofunctional vinyl monomer> Examples of the monofunctional vinyl monomer include monofunctional (meth)acrylic monomers, monofunctional aromatic vinyl monomers, fatty acid vinyl ester monomers, halogenated olefin monomers, vinyl cyanide monomers, unsaturated carboxylic acid monomers, unsaturated polycarboxylic acid ester monomers, unsaturated carboxylic acid amide monomers, and methylolated unsaturated carboxylic acid amide monomers.
[0014] These monofunctional vinyl monomers may be used alone or in combination of two or more.
[0015] Examples of monofunctional (meth)acrylic acid ester monomers include methyl (meth)acrylate (methyl methacrylate, methyl acrylate), ethyl (meth)acrylate, propyl (meth)acrylate, isopropyl (meth)acrylate, n-butyl (meth)acrylate, isobutyl (meth)acrylate, s-butyl (meth)acrylate, t-butyl (meth)acrylate, pentyl (meth)acrylate, isopentyl (meth)acrylate, hexyl (meth)acrylate, heptyl (meth)acrylate, octyl (meth)acrylate, 2-ethylhexyl (meth)acrylate, isooctyl (meth)acrylate, nonyl (meth)acrylate, isononyl (meth)acrylate, decyl (meth)acrylate, isodecyl (meth)acrylate, undecyl (meth)acrylate, dodecyl (meth)acrylate, tridecyl (meth)acrylate, tetradecyl (meth)acrylate, pentadecyl (meth)acrylate, hexyl (meth)acrylate, Examples of such acrylates include (meth)acrylic acid alkyl esters having 1 to 20 carbon atoms in the alkyl group bonded to the ester bond, such as sadecyl, heptadecyl (meth)acrylate, octadecyl (meth)acrylate, isostearyl (meth)acrylate, nonadecyl (meth)acrylate, and eicosyl (meth)acrylate; (meth)acrylic acid esters having an alicyclic structure in the ester moiety, such as cyclohexyl (meth)acrylate, isobornyl (meth)acrylate, and dicyclopentanyl (meth)acrylate; (meth)acrylic acid esters having an epoxy group (glycidyl group) in the ester moiety, such as glycidyl (meth)acrylate; (meth)acrylic acid esters having a hydroxyl group in the ester moiety, such as 2-hydroxyethyl (meth)acrylate and 2-hydroxypropyl (meth)acrylate; and (meth)acrylic acid esters having an amino group in the ester moiety, such as dimethylaminoethyl (meth)acrylate and diethylaminoethyl (meth)acrylate. These monofunctional (meth)acrylic acid ester monomers may be used alone or in combination of two or more.
[0016] Among these monofunctional (meth)acrylic acid ester monomers, those having 1 to 10 carbon atoms in the alkyl group bonded to the ester are methyl (meth)acrylate, ethyl (meth)acrylate, propyl (meth)acrylate, isopropyl (meth)acrylate, n-butyl (meth)acrylate, isobutyl (meth)acrylate, s-butyl (meth)acrylate, t-butyl (meth)acrylate, pentyl (meth)acrylate, isopentyl (meth)acrylate, hexyl (meth)acrylate, heptyl (meth)acrylate, octyl (meth)acrylate, 2-ethylhexyl (meth)acrylate, isooctyl (meth)acrylate, nonyl (meth)acrylate, isononyl (meth)acrylate, and decyl (meth)acrylate, which are versatile and preferable, and in applications requiring heat resistance in particular, cyclohexyl (meth)acrylate, isobornyl (meth)acrylate, and dicyclopentanyl (meth)acrylate are preferable. These monofunctional (meth)acrylic acid ester monomers may be used alone or in combination of two or more.
[0017] Examples of monofunctional aromatic vinyl monomers include styrene, o-methylstyrene, m-methylstyrene, p-methylstyrene (vinyl toluene), ethylvinylbenzene, α-methylstyrene, styrenesulfonates such as sodium styrenesulfonate and ammonium styrenesulfonate, vinylnaphthalene, and allylbenzene. Among these, styrene, α-methylstyrene, and sodium styrenesulfonate are preferred. These monofunctional styrene monomers may be used alone or in combination of two or more.
[0018] Examples of fatty acid vinyl ester monomers include vinyl acetate, vinyl propionate, etc. These fatty acid vinyl ester monomers may be used alone or in combination of two or more. Examples of halogenated olefin monomers include vinyl chloride, vinylidene chloride, tetrafluoroethylene, vinylidene fluoride, etc. These halogenated olefin monomers may be used alone or in combination of two or more. An example of the vinyl cyanide monomer is (meth)acrylonitrile. The unsaturated carboxylic acid monomer includes unsaturated carboxylic acids, their salts or anhydrides, such as (meth)acrylic acid, crotonic acid, maleic acid, fumaric acid, their ammonium or metal salts, maleic anhydride, etc. These unsaturated carboxylic acid monomers may be used alone or in combination of two or more.
[0019] The unsaturated polycarboxylate monomer includes unsaturated dicarboxylate monoesters, their salts, and unsaturated dicarboxylate diesters, such as monobutyl maleate, ammonium or metal salts thereof, dimethyl maleate, etc. These unsaturated polycarboxylate monomers may be used alone or in combination of two or more. Examples of the unsaturated carboxylic acid amide monomer include (meth)acrylamide, diacetone (meth)acrylamide, etc. These unsaturated carboxylic acid amide monomers may be used alone or in combination of two or more. Examples of the methylolated unsaturated carboxylic acid amide monomer include N-methylol acrylamide, N-methylol methacrylamide, methylolated diacetone acrylamide, and ethers of these monomers with alcohols having a carbon number of 1 to 8. These methylolated unsaturated carboxylic acid amide monomers may be used alone or in combination of two or more.
[0020] <Multifunctional vinyl monomer> Examples of the polyfunctional vinyl monomer include polyfunctional (meth)acrylic monomers, polyfunctional aromatic vinyl monomers, and polyfunctional allyl monomers. These polyfunctional vinyl monomers may be used alone or in combination of two or more.
[0021] Examples of the polyfunctional (meth)acrylic monomer include ethylene glycol di(meth)acrylate, propylene glycol di(meth)acrylate, diethylene glycol di(meth)acrylate, triethylene glycol di(meth)acrylate, decaethylene glycol di(meth)acrylate, pentadecaethylene glycol di(meth)acrylate, pentacontahexaethylene glycol di(meth)acrylate, 1,3-butylene di(meth)acrylate, allyl (meth)acrylate, trimethylolpropane tri(meth)acrylate, trimethylolpropane tri(meth)acrylate, and pentaerythritol tetraacrylate. Among these, ethylene glycol di(meth)acrylate and allyl (meth)acrylate are preferred. These polyfunctional (meth)acrylic monomers may be used alone or in combination of two or more.
[0022] Examples of polyfunctional aromatic vinyl monomers include divinylbenzene, divinylnaphthalene, and derivatives of these in which the aromatic ring is substituted with a substituent, etc. These polyfunctional aromatic vinyl monomers may be used alone or in combination of two or more. Examples of the polyfunctional allyl monomer include diallyl phthalate, triallyl cyanurate, etc. These polyfunctional allyl monomers may be used alone or in combination of two or more.
[0023] <Composition of resin particles> In the present invention, it is preferable that the vinyl monomer constituting the resin fine particles contains a polyfunctional vinyl monomer. In the present invention, the vinyl monomer constituting the resin fine particles preferably contains a (meth)acrylic acid ester monomer, where the (meth)acrylic acid ester monomer is one or more selected from the group consisting of monofunctional (meth)acrylic monomers and polyfunctional (meth)acrylic monomers. In the present invention, the vinyl monomer constituting the resin fine particles is preferably a mixture of a monofunctional vinyl monomer and a polyfunctional vinyl monomer.
[0024] The resin fine particles of the present invention are preferably composed of at least one resin selected from the group consisting of (meth)acrylic resins, styrene resins, and (meth)acrylic-styrene resins, which allows the formation of resin fine particles with high light transmittance. The (meth)acrylic resin is a resin obtained by polymerizing one or more types of (meth)acrylic acid ester monomers, or a resin obtained by polymerizing one or more types of (meth)acrylic acid ester monomers and one or more types of vinyl monomers other than (meth)acrylic acid ester monomers and styrene monomers. The styrene-based resin is a resin obtained by polymerizing one or more types of styrene-based monomers, or a resin obtained by polymerizing one or more types of styrene-based monomers and one or more types of vinyl-based monomers other than (meth)acrylic acid ester-based monomers and styrene-based monomers. The (meth)acrylic-styrene-based co-resin is a resin obtained by polymerizing one or more types of (meth)acrylic acid ester-based monomers and one or more types of styrene-based monomers, or a resin obtained by polymerizing one or more types of (meth)acrylic acid ester-based monomers, one or more types of styrene-based monomers, and one or more types of vinyl-based monomers other than those.
[0025] In the present invention, the content of the polyfunctional vinyl monomer in 100 parts by mass of the vinyl monomer constituting the resin microparticles is not particularly limited. For example, the content of the polyfunctional vinyl monomer in 100 parts by mass of the vinyl monomer is 51 parts by mass or more, preferably 60 parts by mass or more, more preferably 70 parts by mass or more, and for example, 100 parts by mass or less, preferably 95 parts by mass or less. When the content of the polyfunctional vinyl monomer in 100 parts by mass of the vinyl monomer constituting the resin fine particles is low, (i) it is not possible to prevent the resin fine particles from falling off the substrate or binder, (ii) it is not possible to impart scratch resistance to the film, and (iii) in the infrared spectrum measured by the ATR method using an infrared spectrophotometer, -1 ~1700cm -1 (iv) the degree of crosslinking of the resin microparticles is reduced, and when the resin microparticles are mixed with a binder and / or a solvent, they swell, increasing the viscosity and reducing coating workability, etc.; (v) because the degree of crosslinking of the resin microparticles is reduced, the resin microparticles may be easily deformed or dissolved when they are mixed with a binder and heated to form a molded product.
[0026] The resin fine particles of the present invention may contain various additives, for example, an antioxidant. The antioxidant is not particularly limited, and examples thereof include sulfur-based antioxidants, phosphorus-based antioxidants, hindered phenol-based antioxidants, lactone-based antioxidants, etc. The antioxidant can be added during polymerization of the resin fine particles.
[0027] <Absorbance ratio> The absorbance ratio is the value at a wave number of 1700 cm obtained from the infrared spectrum of resin fine particles measured by the ATR method using an infrared spectrophotometer. -1 ~1800cm -1 Maximum peak height (maximum absorbance) (A) (hereinafter sometimes referred to as "absorbance (A)"), wavenumber 1600 cm -1 ~1700cm -1The maximum peak height (maximum absorbance) (B) (hereinafter sometimes referred to as "absorbance (B)") was determined, and then the absorbance ratio was calculated using (Equation 1). (Formula 1) Absorbance ratio = (B) / (A)
[0028] The absorbance (A) corresponds to the absorption spectrum mainly derived from the C=O stretching vibration of the ester group. -1 ~1800cm -1 Even if other absorption spectra overlap at 1700 cm, no peak separation is performed. -1 and 1800cm -1 The line connecting these points is the baseline, 1700cm -1 and 1800cm -1 The maximum absorbance between the two peaks is indicated. The absorbance (B) corresponds to the absorption spectrum mainly due to the alkene C=C stretching vibration. -1 ~1700cm -1 Even if other absorption spectra overlap at 1600 cm, no peak separation is performed. -1 and 1700cm -1 The line connecting these points is the baseline, and the distance is 1600 cm. -1 and 1700cm -1 The maximum absorbance between the two peaks is indicated. In the present invention, the absorbance (A) and the absorbance (B) can be determined, for example, by using the method described in the section [Examples].
[0029] The absorbance ratio of the resin fine particles of the present invention is 0.020 or more, preferably 0.025 or more, and 0.060 or less, preferably 0.055 or less. If the absorbance ratio is less than 0.020, the resin fine particles may fall off from the substrate or binder, and the film may not be able to be scratch-resistant. If the absorbance ratio is more than 0.060, the resin fine particles may aggregate, and the resin fine particles may fall off from the substrate or binder, and the film may not be able to be scratch-resistant. The absorbance (B) of the resin fine particles of the present invention is not particularly limited, but is, for example, 0.0040 or more, preferably 0.0045 or more, and for example, 0.0120 or less, preferably 0.0100 or less.
[0030] <Amount of unreacted vinyl monomer in resin particles> The amount of unreacted vinyl monomer in the resin microparticles is not particularly limited. For example, the amount of the total vinyl monomer used in preparing the resin microparticles is 100% by mass, and the amount is 1.0% by mass or less, preferably 0.9% by mass or less, more preferably 0.8% by mass or less. If the amount of unreacted vinyl monomer exceeds 1.0% by mass, problems such as deterioration of optical properties, generation of residual odor, environmental pollution, generation of foreign matter (such as resin scum) when using the resin microparticles may occur. In the present invention, the amount of unreacted vinyl monomer in the resin fine particles can be determined, for example, by using the method described in the section [Examples].
[0031] <Moisture content> The moisture content in the resin microparticles is not particularly limited, but it is preferable that the moisture content is low and dry.For example, the moisture content is 2.0% by mass or less, preferably 1.0% by mass or less, more preferably 0.5% by mass or less, based on 100% by mass of the whole resin microparticles.If the moisture content exceeds 2.0% by mass, unevenness may occur during molding of the resin microparticle-containing composition or during coating film formation, and problems such as deterioration of optical properties may occur. In the present invention, the water content of the resin fine particles can be determined, for example, by using the method described in the section [Examples].
[0032] <Volume average particle size> In the present invention, the volume average particle diameter of the resin microparticles is not particularly limited. For example, it is 0.01 μm or more, preferably 0.1 μm or more, and for example, it is 20 μm or less, preferably 15 μm or less, more preferably 10 μm or less. By making the volume average particle diameter within this range, when it is used as an additive for a film, it can improve optical properties. In the present invention, the volume average particle size of the resin fine particles refers to the arithmetic average of the volume-based particle size distribution obtained, for example, by the method described in the section [Examples].
[0033] <Coefficient of variation of particle size of resin particles> In the present invention, the coefficient of variation of the particle diameter is not particularly limited. For example, it is 35.0% or less, preferably 33.0% or less. By setting the coefficient of variation of the particle diameter of the resin fine particles within this range, the dispersion uniformity of the resin fine particles can be further improved. The coefficient of variation of the particle size of the resin fine particles of the present invention is calculated by the following formula. Coefficient of variation of particle size of resin microparticles = (Standard deviation of volume-based particle size distribution of resin microparticles ÷ Volume average particle size of resin microparticles) × 100
[0034] <Residual surfactant amount> The amount of the residual surfactant in the resin microparticles of the present invention relative to 100 parts by mass of the resin microparticles is not particularly limited and is appropriately set according to the purpose and use. For example, it is 0.01 parts by mass or more, preferably 0.03 parts by mass or more, more preferably 0.05 parts by mass or more, and for example, it is in the range of 1 part by mass or less, preferably 0.7 parts by mass or less, more preferably 0.5 parts by mass or less. When a surfactant is used during polymerization, if the amount of the residual surfactant is less than 0.01 part by mass, the process becomes complicated, which may be disadvantageous in terms of costs, etc. If the amount of the residual surfactant exceeds 1 part by mass, free surfactant will be present when the resin fine particles are blended into a coating composition, and the particles will tend to easily fall off. In the present invention, the amount of remaining surfactant can be determined, for example, by the method described in the section [Examples].
[0035] [Method of manufacturing resin particles] The method for producing the resin microparticles of the present invention is not particularly limited. For example, (i) a polymerization step of polymerizing a vinyl monomer in a liquid medium in the presence of a surfactant and a polymerization initiator to obtain a crude product containing resin fine particles containing the surfactant and the medium; (ii) a solid-liquid separation step in which the medium contained in the crude product is removed using a filter; (iii) a washing step of contacting the resin microparticles with a washing solution and then removing the washing solution; (iv) if necessary, a drying step and / or a classification step; A method comprising the steps of: Each step of the method for producing resin fine particles of the present invention will be described in detail below.
[0036] <Polymerization process> In the method for producing resin microparticles of the present invention, the polymerization method in the polymerization step is not particularly limited. For example, a polymerization method using a vinyl monomer, a polymerization initiator, and a liquid medium, and optionally using a surfactant, such as suspension polymerization, seed polymerization, seed emulsion polymerization, emulsion polymerization, soap-free polymerization, mini-emulsion polymerization, and dispersion polymerization, can be mentioned. In these polymerization methods, it is a known technology that the structure of resin particles can be controlled by adding various organic solvents for polymerization, but in the present invention, polymerization in the absence of organic solvent is preferred. In the case of polymerization in a system in which an organic solvent is present, the number of remaining reactive groups tends to decrease, which is thought to be because the polymer chain during polymerization swells in the solvent, improving the driving force and increasing the frequency of contact with radicals in the system, but this is not limited to this. Examples of the vinyl monomer used in the polymerization of the resin fine particles of the present invention include the vinyl monomers described in the section [Resin fine particles].
[0037] (Polymerization initiator) The polymerization initiator used when preparing the resin microparticles of the present invention by a polymerization method such as emulsion polymerization, seed emulsion polymerization, soap-free polymerization, etc., is not particularly limited. For example, a thermally decomposable water-soluble polymerization initiator is used. For example, persulfates such as potassium persulfate, ammonium persulfate, lithium persulfate, and sodium persulfate, hydrogen peroxide, and water-soluble azo-based polymerization initiators are used as the thermally decomposable water-soluble polymerization initiator. For the water-soluble azo-based polymerization initiator, a polymerization initiator that has been conventionally used for emulsion polymerization or the like can be used, and a newly developed polymerization initiator used for emulsion polymerization or the like can also be used.Examples of the water-soluble azo polymerization initiator include VA-080 (2,2'-azobis(2-methyl-N-(1,1-bis(hydroxymethyl)-2-hydroxyethyl)propionamide)), VA-086 (2,2'-azobis(2-methyl-N-(2-hydroxyethyl)-propionamide)), VA-057 (2,2'-azobis(2-(N-(2-carboxyethyl)amidino)propane)), VA-058 (2,2'-azobis(2-(3,4,5,6,-tetrahydropyrimidine)), VA-060 (2,2'-azobis(2-(1-(2-hydroxyethyl)-2-imidazolin-2-yl)propane) dihydrochloride), V-50 (2,2'-azobis(2-amidinopropane) dihydrochloride), V-501 (4,4'-azobis(4-cyanopentanoic acid)), VA-082 (2,2'-azobis(2-methyl-N-(1,1-bis(hydroxymethyl)ethyl)propionamide)), VA-085 ( 2,2'-Azobis(2-methyl-N-(2-(1-hydroxybutyl))-propionamide)), VA-044 (2,2'-Azobis(2-(2-imidazolin-2-yl)propane) dihydrochloride), VA-046B (2,2'-Azobis(2-(2-imidazolin-2-yl)propane) disulfate dihydrate), VA-061 (2,2'-Azobis(2-(2-imidazolin-2-yl)propane)) (all manufactured by Fujifilm Wako Pure Chemical Industries, Ltd.), 2,2'-Azobis(2-amidinopropane)
[0113] One or more selected from the group consisting of 2,2'-azobis(2-(1-(2-hydroxyethyl)-2-imidazolin-2-yl)propane) dihydrochloride, 2,2'-azobis(1-imino-1-pyrrolidino-2-ethylpropane) dihydrochloride, 2,2'-azobis(1-imino-1-pyrrolidino-2-methylpropane) dihydrochloride, 2,2'-azobis(2-methyl-N-(1,1-bis(hydroxymethyl)-2-hydroxyethyl)propionamide) and the like can be mentioned. Water-soluble azo-based polymerization initiators are preferred because they have little effect on the pH of the slurry after polymerization and can suppress particle aggregation and the generation of coarse particles due to a decrease in dispersibility.Furthermore, from the viewpoint of improving the dispersibility of the resin microparticles, those having a hydroxyl group at the terminal of the polymerization initiator are preferred. Among the water-soluble azo-based polymerization initiators, those not containing halogen are more preferable from the viewpoint of reducing the electrical conductivity of the resin fine particle dispersion, and VA-086 and VA-057 are particularly preferable because of their good water solubility.
[0038] When the resin is prepared by a polymerization method such as suspension polymerization, seed polymerization, or mini-emulsion polymerization, any known polymerization initiator can be used without particular limitation, but it is preferable to use a thermally decomposable oil-soluble polymerization initiator. For example, organic peroxides such as cumene hydroperoxide, di-tert-butyl peroxide, dicumyl peroxide, benzoyl peroxide, lauroyl peroxide, dimethylbis(tert-butylperoxy)hexane, dimethylbis(tert-butylperoxy)hexyne-3, bis(tert-butylperoxyisopropyl)benzene, bis(tert-butylperoxy)trimethylcyclohexane, butyl-bis(tert-butylperoxy)valerate, 2-ethylhexaneperoxy acid tert-butyl, dibenzoyl peroxide, paramenthane hydroperoxide, and tert-butyl peroxybenzoate; 2,2'-azobisisobutyronitrile, 2,2'-azobis(2-methylbutyronitrile), 2,2'-azobis(2-isopropyl ... 2,2'-azobis(2,3-dimethylbutyronitrile), 2,2'-azobis(2,4-dimethylbutyronitrile), 2,2'-azobis(2-methylcapronitrile), 2,2'-azobis(2,3,3-trimethylbutyronitrile), 2,2'-azobis(2,4,4-trimethylvaleronitrile), 2,2'-azobis(2,4-dimethylvaleronitrile), 2,2'-azobis(4-methoxy-2,4-dimethylvaleronitrile) nitrile), 2,2'-azobis(4-ethoxy-2,4-dimethylvaleronitrile), 2,2'-azobis(4-n-butoxy-2,4-dimethylvaleronitrile), 1,1'-azobis(cyclohexane-1-carbonitrile), 2-(carbamoylazo)isobutyronitrile, 4,4'-azobis(4-cyanopentanoic acid), and other nitrile-azo compounds.
[0039] The amount of the polymerization initiator used can be appropriately determined depending on the type of the polymerization initiator, and is not particularly limited. For example, the amount is 0.1 parts by mass or more, preferably 0.3 parts by mass or more, and for example, 5 parts by mass or less, preferably 3 parts by mass or less, relative to 100 parts by mass of the total amount of all monomers used in the polymerization.
[0040] (Surfactant) The surfactant that may be used as necessary to prepare the resin fine particles of the present invention is not particularly limited. In the polymerization of the resin fine particles of the present invention, an anionic surfactant can be used. The anionic surfactant is classified into a reactive surfactant having a reactive group such as a vinyl group and a non-reactive surfactant having no reactive group. As the anionic non-reactive surfactant, any of the known anionic surfactants such as fatty acid salt type, sulfate ester salt type, sulfonate salt type, and phosphate ester salt type can be used. For example, alkyl sulfate salts such as sodium lauryl sulfate and ammonium lauryl sulfate; alkyl benzene sulfonates such as sodium dodecyl benzene sulfonate; dialkyl sulfosuccinate salts such as sodium dioctyl sulfosuccinate and sodium di(2-ethylhexyl) sulfosuccinate; fatty acid soaps such as sodium oleate and castor oil potassium soap; alkyl naphthalene sulfonates; alkanesulfonates; alkenyl succinates such as sodium (mono- or di-) alkenyl succinate; alkyl phosphate salts; naphthalene sulfonate-formaldehyde condensates; polyoxyethylene alkyl phenyl ether sulfate salts; polyoxyethylene alkyl ether sulfate salts such as sodium polyoxyethylene lauryl ether sulfate; polyoxyethylene alkyl sulfate esters; polyoxyethylene styrenated phenyl ether sulfate salts such as ammonium polyoxyethylene styrenated phenyl ether sulfate; polyoxyethylene alkyl phenyl ether phosphate salts such as polyoxyethylene nonyl phenyl ether phosphate (for example, sodium polyoxyethylene nonyl phenyl ether phosphate); and the like. Among these, as the phosphate-based anionic surfactant, for example, one or more types selected from commercially available products such as Plysurf (AL, A210G, A208F, etc.) manufactured by Daiichi Kogyo Seiyaku Co., Ltd. and Phosphanol (LO-529, etc.) manufactured by Toho Chemical Industry Co., Ltd., and salts thereof can be used. Examples of the anionic reactive surfactant include JS-20 and RS-3000 of ELEMINOL (registered trademark) manufactured by Sanyo Chemical Industries, Ltd., KH-10, KH-1025, KH-05, HS-10, HS-1025, BC-0515, BC-10, BC-1025, BC-20, BC-2020, AR-1025, AR-2025 of AQUALON (registered trademark) manufactured by Daiichi Kogyo Seiyaku Co., Ltd., S-120, S-180A, S-180, PD-104 of LATEMUL (registered trademark) manufactured by Kao Corporation, SR-1025, SE-10N of ADEKA REASOAP (registered trademark) manufactured by ADEKA Corporation, etc. Among them, those having an oxyalkylene chain in the molecular chain are preferred from the viewpoint of improving the dispersibility of particles.
[0041] In the polymerization of the resin fine particles of the present invention, a nonionic surfactant can be used. Nonionic surfactants are classified into reactive surfactants having a reactive group such as a vinyl group and non-reactive surfactants having no reactive group. As the nonionic non-reactive surfactant, any of known nonionic surfactants such as ester type, ether type, ester-ether type, etc. can be used. For example, one or more selected from the group consisting of polyoxyalkylene alkyl ethers such as polyoxyalkylene tridecyl ethers having an alkylene group with 3 or more carbon atoms; fatty acid esters such as sorbitan fatty acid esters, glycerin fatty acid esters, isopropyl palmitate, and sorbitan trioleate; polyoxyethylene styrenated phenyl ether; polyoxyethylene styrenated phenyl ether (for example, Noigen EA series manufactured by Daiichi Kogyo Seiyaku Co., Ltd.); polyoxyethylene alkyl ethers such as polyoxyethylene tridecyl ether; polyoxyethylene alkyl phenyl ethers such as polyoxyethylene octylphenyl ether; polyoxyethylene fatty acid esters; polyoxyethylene sorbitan fatty acid esters such as polyoxyethylene sorbitan monolaurate; polyoxyethylene alkylamines; oxyethylene-oxypropylene block polymers; polyoxyethylene alkyl phenyl ether phosphates such as polyoxyethylene nonylphenyl ether phosphate; polyoxyethylene styrenated phenyl ether phosphate; polyoxyethylene alkyl ether phosphate; and the like can be mentioned. Examples of the nonionic reactive surfactant include at least one selected from the group consisting of alkyl ether surfactants (e.g., Adeka Reasoap ER-10, ER-20, ER-30, ER-40 manufactured by ADEKA Corporation, and Latemul PD-420, PD-430, PD-450 manufactured by Kao Corporation); alkyl phenyl ether surfactants or alkyl phenyl ester surfactants (e.g., Aqualon RN-10, RN-20, RN-30, RN-50, AN-10, AN-20, AN-30, AN-5065 manufactured by Daiichi Kogyo Seiyaku Co., Ltd., and Adeka Reasoap NE-10, NE-20, NE-30, NE-40 manufactured by ADEKA Corporation); and (meth)acrylate sulfate surfactants (e.g., RMA-564, RMA-568, RMA-1114 manufactured by Nippon Nyukazai Co., Ltd.). Among these, surfactants having an oxyalkylene chain in the molecular chain are preferred from the viewpoint of the dispersion stability of the particles.
[0042] The amount of surfactant used is not particularly limited, but is, for example, 0.01 to 10 parts by mass relative to 100 parts by mass of vinyl monomer. If the total amount of surfactant is less than the above range, the polymerization stability may be reduced, and it may be difficult to adjust the amount of surfactant contained in the resin fine particles. If the amount of surfactant used is more than the above range, it is cost-uneconomical, and it may be difficult to adjust the amount of each surfactant contained in the resin fine particles to the specified range.
[0043] (Liquid medium) The liquid medium used to prepare the resin microparticles of the present invention is not particularly limited. For example, any of water, organic solvents, and mixtures thereof can be used. In the present invention, an aqueous medium is preferred, and for example, water, lower alcohols having 5 or less carbon atoms such as methyl alcohol and ethyl alcohol, and mixtures of water and lower alcohols can be used.
[0044] (Polymerization method) The polymerization method of the vinyl monomer is not particularly limited, and examples thereof include known polymerization methods such as suspension polymerization, emulsion polymerization, seed polymerization, seed emulsion polymerization, soap-free polymerization, mini-emulsion polymerization, and dispersion polymerization. By the suspension polymerization, it is possible to obtain fine resin particles having a small particle size and small variation in particle size (relatively uniform particle size). By the emulsion polymerization, it is possible to reduce the variation in particle size of the obtained resin fine particles. The resin fine particles obtained by seed polymerization have little variation in particle size, and when used for optical components such as antiglare films and light diffusion films, the optical properties such as antiglare properties and light diffusion properties of the optical components can be improved. Since the particle size of the resulting resin fine particles varies little, suspension polymerization, emulsion polymerization, and seed polymerization are preferred, and seed polymerization is most preferred. A general method for seed polymerization will be described below, but the polymerization method in the production method of the present invention is not limited to this method.
[0045] In the seed polymerization, first, an emulsion (suspension) containing an aqueous medium, a vinyl monomer, and a surfactant is prepared. Here, the aqueous medium is water or a mixture of water and an organic solvent. The emulsion (suspension) can be prepared by a known method. For example, the emulsion can be obtained by adding a vinyl monomer and a surfactant to an aqueous medium and dispersing the mixture with a microemulsifier such as a homogenizer, an ultrasonic processor, or a Nanomizer (registered trademark). Incidentally, it is preferable that the particle size of the droplets of the vinyl monomer present in the obtained emulsion is smaller than the particle size of the seed particles to be added subsequently, since the droplets are efficiently absorbed by the seed particles.
[0046] Next, seed particles are added to the resulting emulsion (suspension). The seed particles may be added to the emulsion as they are, or may be added to the emulsion in a form dispersed in an aqueous medium. When the seed particles are added to the emulsion, the vinyl monomer is absorbed into the seed particles. As a method for causing the seed particles to absorb the vinyl monomer, a method of stirring the emulsion at room temperature (about 20°C) for 1 to 12 hours is usually mentioned. In addition, in order to promote the absorption of the vinyl monomer into the seed particles, the emulsion may be heated to about 30 to 50°C. When the vinyl monomer is absorbed into the seed particles, the seed particles swell. The mixing ratio of the vinyl monomer to the seed particles is preferably within a range of, for example, 5 to 300 parts by mass of the vinyl monomer per 1 part by mass of the seed particles. The completion of the absorption of the vinyl monomer into the seed particles can be determined by observing the particle diameter with an optical microscope. Next, the vinyl monomer absorbed in the seed particles is polymerized to obtain resin fine particles. Note that the step of absorbing the vinyl monomer into the seed particles and polymerizing the same may be repeated several times to obtain resin fine particles. In the polymerization of the vinyl monomer, a polymerization initiator may be used as necessary. The polymerization initiator may be mixed with the vinyl monomer in advance and then dispersed in the aqueous medium, or both the polymerization initiator and the vinyl monomer may be dispersed separately in the aqueous medium.
[0047] The polymerization temperature and polymerization time of the seed polymerization can be appropriately selected depending on the type of vinyl monomer and the type of polymerization initiator used as necessary. The polymerization temperature is, for example, 25 to 110° C., and the polymerization time is, for example, 1 to 12 hours. The polymerization reaction of the seed polymerization may be carried out under an atmosphere of an inert gas (eg, nitrogen) that is inert to the polymerization. In the production of the resin fine particles of the present invention, the polymerization reaction of the seed polymerization is preferably carried out at elevated temperature after the vinyl monomer and the polymerization initiator used if necessary are completely absorbed into the seed particles.
[0048] In the seed polymerization, a polymer dispersion stabilizer may be added to the polymerization reaction system to improve the dispersion stability of the resin fine particles. Examples of the polymer dispersion stabilizer include polyvinyl alcohol, polycarboxylic acid, cellulose, polyvinylpyrrolidone, etc. In addition, the polymer dispersion stabilizer may be used in combination with an inorganic water-soluble polymer compound such as sodium tripolyphosphate. Of these polymer dispersion stabilizers, it is preferable to use polyvinyl alcohol and polyvinylpyrrolidone. The amount of the polymer dispersion stabilizer added is preferably within the range of 1 to 10 parts by mass per 100 parts by mass of the vinyl monomer. In order to suppress the generation of emulsion polymerization products (resin fine particles having too small a particle size) in the aqueous medium during the polymerization reaction, a water-soluble polymerization inhibitor such as nitrites such as sodium nitrite, sulfites, hydroquinones, ascorbic acids, water-soluble vitamin Bs, citric acid, polyphenols, etc. may be added to the aqueous medium. When a polymerization inhibitor is used, the amount added is preferably within a range of 0.02 to 0.2 parts by mass per 100 parts by mass of the vinyl monomer.
[0049] The method for producing seed particles used in seed polymerization is not particularly limited, and dispersion polymerization, emulsion polymerization, soap-free emulsion polymerization (emulsion polymerization without using a surfactant as an emulsifier), seed polymerization, suspension polymerization, etc. can be used.
[0050] <Solid-liquid separation process> The solid-liquid separation process in producing the resin microparticles of the present invention is a process in which the medium, etc. are removed from the crude product containing the resin microparticles, surfactant and medium obtained in the polymerization process using a filter equipped with a filter material, and the resin microparticles are separated into solid and liquid.
[0051] The filter is not particularly limited. For example, a pressure filter including a pressure vessel, a filter medium disposed on the inner bottom of the pressure vessel, and a compressed gas supplying device that supplies compressed gas into the pressure vessel can be used. The filter material is not particularly limited as long as it can reliably collect resin fine particles.For example, one or more selected from the group consisting of filter cloth such as woven cloth or nonwoven cloth made of natural fiber or synthetic fiber, wire mesh made of sintered metal, nonwoven cloth made of sintered metal, filter plate (porous plate) made of natural fiber or glass fiber, mesh made of synthetic resin, filter paper, glass fiber filter, etc. can be mentioned, and filter cloth is particularly preferred. In the solid-liquid separation process, the amount of residual surfactant and non-volatile components in the resin microparticles can be easily adjusted by controlling the amount of medium passing through the filter material per unit time, the pressurization conditions, the drainage speed when removing the medium, etc.
[0052] <Cleaning process> The washing step in the production of the resin microparticles of the present invention is a step in which the resin microparticles after the solid-liquid separation step are brought into contact with a washing liquid, and then the washing liquid is removed to obtain washed resin microparticles. In the washing process, the cake of resin microparticles obtained in the solid-liquid separation process is immersed in a washing solution having a volume 10 times or less, preferably 1.5 to 7 times, the volume of the resin microparticle cake, and then the washing process of removing the washing solution is repeated as necessary, thereby controlling the amount of residual surfactant in the resin microparticles, etc. An example of a method for removing the washing solution is to use a centrifuge to perform a washing process in which the washing solution is centrifuged and removed, and the washing process is repeated as necessary. In addition, for example, a pressurized filter is used to wash the cake of resin particles on the filter medium by contacting the washing liquid, which eliminates the short path of the washing liquid, reduces the amount of washing liquid used, and enables efficient washing. For example, the washing liquid can be removed by introducing compressed gas into the pressurized filter to apply pressure, thereby contacting the cake with the washing liquid and discharging the washing liquid after washing as filtrate. In the washing process, the amount of residual surfactant and non-volatile components contained in the resin particles can be adjusted by adjusting the number of centrifugations, the amount of washing liquid added, the amount of medium passing through the filter medium (discharge amount), etc.
[0053] The washing liquid used in the washing step is preferably an aqueous medium, and examples thereof include water, lower alcohols having 5 or less carbon atoms such as methyl alcohol and ethyl alcohol, and mixtures thereof. In particular, it is preferable to use the same medium as that used in the polymerization step. The weight of the washing liquid used in the washing step is 10 times or less, and preferably 1.5 to 7 times, the weight of the resin fine particles to be washed, which can prevent the surfactant from being eluted more than necessary in the washing step.
[0054] In the washing step, the filtration rate of the washing liquid is not particularly limited and may be, for example, 0.025 to 0.095 kg / min m 2 The range is. The temperature of the washing solution used for washing is a temperature at which the surfactant used during polymerization is sufficiently eluted, for example, in the range of 40 to 80°C. The washing process is preferably terminated when the conductivity of the washing liquid that has passed through the filter medium becomes 2.0 times or less than the conductivity of the washing liquid before it was introduced into the filter, and the internal pressure of the pressurized filter becomes 2 / 3 or less of the pressure during pressurization.
[0055] <Drying process and classification process> The resin microparticles obtained in the washing step are preferably dried in a dryer to remove the washing liquid and classified as necessary. The dryer is not particularly limited, but for example, a spray dryer, freeze dryer, or a vacuum agitation dryer (disintegration dryer) incorporating an agitation blade is preferable, and an appropriate drying device can be selected depending on the particle size and composition. The washing liquid is almost completely removed by drying, and the resin microparticles can be classified (preferably air current classification) as necessary to become usable as a product. The drying conditions in the present invention are appropriately adjusted depending on the capacity and capacity of the dryer used, etc. For example, the degree of vacuum (relative to atmospheric pressure) can be set to -0.001 to -0.5 MPa, the drying temperature to 40 to 80°C, and the drying time to 4 to 10 hours (hr). In the present invention, in the drying step, the surfactant is dissolved from the surface of the resin fine particles into water, and then a crushing dryer is used to remove non-volatile components together with the water content, thereby making it possible to adjust the amount of the residual surfactant in the resin fine particles. For example, by pre-warming the washed resin microparticle cake, it is possible to easily adjust the surfactant on the particle surface to a specified amount. Furthermore, the non-volatile components are sheared and most of them are separated off by the crushing and drying process. The remaining surfactant effectively modifies the resin microparticle surface, resulting in resin microparticles with excellent dispersion uniformity and improved dispersibility. According to such a method for producing resin microparticles, it is possible to remove an appropriate amount of residual surfactant attached to the resin microparticles during the polymerization process together with the medium and cleaning liquid, and further, it is possible to make the content (residual amount) of non-volatile components appropriate.
[0056] [Composition containing fine resin particles] The resin fine particle-containing composition of the present invention contains the resin fine particles of the present invention, a photopolymerization initiator, and an ultraviolet-curable resin.
[0057] <Photopolymerization initiator> The photopolymerization initiator contained in the resin microparticle-containing composition of the present invention is not particularly limited as long as it is a compound that can generate radicals in the composition by irradiation with light or ultraviolet rays and initiate polymerization of the ultraviolet curable resin. It is preferable to use a photopolymerization initiator that is suitable for the ultraviolet curable resin to be used. As the photopolymerization initiator, for example, one or more selected from the group consisting of acetophenones, benzoins, benzophenones, phosphine oxides, ketals, α-hydroxyalkylphenones, α-aminoalkylphenones, anthraquinones, thioxanthones, azo compounds, peroxides, 2,3-dialkyldione compounds, disulfide compounds, fluoroamine compounds, aromatic sulfonium compounds, onium salts, borate salts, active halogen compounds, α-acyloxime esters, and the like can be used. The amount of the photopolymerization initiator used is, for example, 0.5 parts by mass or more, preferably 1.0 part by mass or more, and for example, 20.0 parts by mass or less, preferably 5.0 parts by mass or less, relative to 100 parts by mass of the ultraviolet-polymerizable resin.
[0058] <Ultraviolet curable resin> The ultraviolet-curable resin contained in the resin microparticle-containing composition of the present invention is appropriately selected according to the required properties such as transparency, dispersibility of resin microparticles, light resistance, moisture resistance, heat resistance, etc., and is not particularly limited. For example, it may contain one or more kinds selected from the group consisting of polyfunctional (meth)acrylate resins, polyfunctional urethane (meth)acrylate resins, polyfunctional polyester (meth)acrylate resins, epoxy (meth)acrylate resins, alkyd resins, etc. The ultraviolet-curable resin is preferably one containing a polyfunctional (meth)acrylate resin, and more preferably one containing a polyhydric alcohol polyfunctional (meth)acrylate having three or more (meth)acryloyl groups in one molecule. Examples of polyhydric alcohol polyfunctional (meth)acrylates having three or more (meth)acryloyl groups in one molecule include one or more selected from the group consisting of trimethylolpropane tri(meth)acrylate, trimethylolethane tri(meth)acrylate, 1,2,4-cyclohexane tri(meth)acrylate, pentaglycerol triacrylate, pentaerythritol tetra(meth)acrylate, pentaerythritol tri(meth)acrylate, dipentaerythritol triacrylate, dipentaerythritol pentaacrylate, dipentaerythritol tetra(meth)acrylate, dipentaerythritol hexa(meth)acrylate, tripentaerythritol triacrylate, and tripentaerythritol hexaacrylate.
[0059] The resin fine particle-containing composition may contain components other than the resin fine particles, the photopolymerization initiator, and the ultraviolet-curable resin, as necessary. For example, it may contain resin particles and resins other than ultraviolet-curable resins (one or more selected from the group consisting of vinyl resins such as cellulose-based resins, vinyl acetate-based resins, vinyl chloride-based resins, vinylidene chloride-based resins, acetal-based resins, (meth)acrylic-based resins, polystyrene-based resins, polyamide resins, linear polyester resins, polycarbonate resins, etc.). Also, for example, a reactive diluent may be included as a solvent. The reactive diluent may be one or more vinyl monomers. The vinyl monomer used as the reactive diluent may be one or more monofunctional (meth)acrylic monomers or polyfunctional (meth)acrylic monomers used in the polymerization of the resin microparticles of the present invention. Furthermore, the ink may contain inorganic particles such as silica, a colorant, an organic solvent, etc. The amount of the organic solvent is preferably small, and it is usually preferable to use no organic solvent.
[0060] The amount of the resin microparticles in the resin microparticle-containing composition is not particularly limited, and is, for example, 2 parts by mass or more, preferably 4 parts by mass or more, more preferably 6 parts by mass or more, and 300 parts by mass or less, preferably 200 parts by mass or less, more preferably 100 parts by mass or less, relative to 100 parts by mass of the solid content of the ultraviolet curable resin. By setting the amount of resin microparticles to 2 parts by mass or more per 100 parts by mass of solid content of the ultraviolet curable resin, the optical properties such as matte property of the layer (coating film) formed by the resin microparticle-containing resin composition can be fully exhibited, and the optical properties such as anti-glare property and light diffusion property of the optical member formed by coating the resin microparticle-containing resin composition on a substrate can be fully obtained. In addition, by setting the amount to 300 parts by mass or less, it becomes easier to obtain a sufficient linear transmittance of the layer (coating film) formed by the resin microparticle-containing composition.
[0061] The method for applying the resin fine particle-containing composition to the substrate is not particularly limited. For example, known coating methods such as bar coating, blade coating, spin coating, reverse coating, die coating, spray coating, roll coating, gravure coating, microgravure coating, lip coating, air knife coating, and dip coating can be used.
[0062] After the resin fine particle-containing composition is applied onto the substrate to form a layer of the resin composition, it can be dried and cured by irradiating it with active energy rays. Examples of the active energy rays that can be used include ultraviolet rays and infrared rays emitted from light sources such as LEDs and high-pressure mercury lamps, electron beams emitted from electron beam accelerators, α rays, β rays, and γ rays. The thickness (dry thickness) of the layer (coating film) formed by the resin fine particle-containing resin composition is not particularly limited and can be appropriately adjusted depending on the purpose, desired properties, etc. For example, it is 1 μm or more, preferably 3 μm or more, and for example, 10 μm or less, preferably 7 μm or less.
[0063] [Applications of resin particles] The resin microparticles of the present invention can be used for various purposes other than the resin microparticle-containing composition. For example, a molding resin composition containing the resin microparticles and a resin can be formed, and the molding resin composition can be used to obtain optical films such as antiglare films and light diffusion films, optical members such as light diffusers, and in particular antiglare members. Furthermore, the resin particles themselves or a mixture of the resin particles and a resin can be molded to obtain a resin molded product.
[0064] For example, the resin fine particle-containing composition may be applied to a substrate to form a layer, thereby forming an optical member. Examples of the optical member include a light diffusion film or an antiglare film for light diffusion or antiglare purposes. The substrate is preferably transparent. For example, the substrate may be glass, polyester resin, cellulose resin, polycarbonate resin, (meth)acrylic resin, cyclic polyolefin resin, a mixture containing one or more of these resins, or a laminate of these resins. Among these, those with a particularly low birefringence are preferably used. Furthermore, the above-mentioned substrates may have an easy-adhesion layer of a (meth)acrylic resin, a polyurethane resin, or the like provided on at least one surface thereof for use as the substrate. The thickness of the substrate can be appropriately determined, but is generally within the range of 10 to 500 μm in terms of strength, workability such as handling, thinness, etc. It is preferably 20 to 300 μm, and more preferably 30 to 200 μm. The substrate may contain additives such as ultraviolet absorbing agents, infrared absorbing agents, antistatic agents, refractive index adjusting agents, and enhancers.
[0065] For example, the resin microparticles of the present invention can be used alone or in combination with other resins to prepare resin molded products by various molding methods. As the other resins, transparent resins can be preferably used, and in the resin molded products, the resin microparticles can function as light diffusing particles. The resin molded article functions as a light diffuser such as a light diffusion plate, and can be used as an LED lighting cover, etc. The transparent resin may be, for example, one or more selected from the group consisting of (meth)acrylic resins, polycarbonate resins, polystyrene resins, (meth)acrylic-styrene resins (copolymers of (meth)acrylic acid esters and styrene), etc. Among these, polystyrene resins or (meth)acrylic-styrene resins are preferred. When preparing a resin molded product from the resin fine particles of the present invention and a transparent resin, the amount of the resin fine particles contained in the resin molded product can be in the range of 0.01 to 5 parts by mass, preferably 0.1 to 5 parts by mass, per 100 parts by mass of the transparent resin. The resin molded product may contain additives such as ultraviolet absorbers, antioxidants, heat stabilizers, light stabilizers, and fluorescent whitening agents, as necessary. The thickness, shape, etc. of the resin molded body can be appropriately selected depending on the application.
[0066] The resin molded body can be obtained by melt-kneading the transparent resin and the resin fine particles with a single screw extruder, a twin screw extruder, or the like. The resin composition obtained by melt-kneading may be molded into a plate shape through a T-die and a roll unit to obtain a resin molded body. Furthermore, the resin composition obtained by melt-kneading may be pelletized, and the pellets may be molded by injection molding, press molding, or the like to obtain a resin molded body. The resin molded article containing the resin fine particles of the present invention has excellent dispersion uniformity of the resin fine particles, and exhibits optical properties such as uniform light diffusibility and antiglare properties. EXAMPLES
[0067] The present invention will be described below with reference to examples and comparative examples, but the present invention is not limited thereto. Unless otherwise specified, "%" means "% by mass" and "parts" means parts by mass.
[0068] [Measurement method] <Maximum absorbance and absorbance ratio> The measurements were performed using a Thermo SCIENTIFIC Fourier transform infrared spectrophotometer "Nicoet iS10" connected to a Thermo SCIENTIFIC "Smart-iTR" as an ATR accessory. The conditions for the infrared spectroscopic analysis ATR measurement are as follows.
[0069] (Measurement conditions) Measurement equipment: Fourier transform infrared spectrophotometer Nicolet iS10 (Thermo Scientific) and single reflection horizontal ATR Smart-iTR (Thermo Scientific) ATR crystal: Diamond with ZnSe lens, angle = 42° ·Measurement method: Single ATR method ·Measurement wavenumber range: 4000cm -1 ~650cm -1 Wavenumber dependence of measurement depth: Not corrected Detector: Deuterated triglycine sulfate (DTGS) detector and KBr beam splitter ·Resolution: 4cm -1 - Number of measurements: 16 (same as for background measurement)
[0070] In the ATR method, the intensity of the infrared absorption spectrum obtained by measurement varies depending on the degree of contact between the sample and the high refractive index crystal. Therefore, the maximum load that can be applied by the ATR accessory "Smart-iTR" was applied to make the degree of contact almost uniform before performing the measurement. The infrared absorption spectrum obtained under the above conditions was processed as follows to obtain the peak at wavenumber 1700 cm -1 ~1800cm -1 Maximum peak height (maximum absorbance) (A) and wavenumber 1600 cm -1 ~1700cm -1 The maximum peak height (maximum absorbance) (B) was determined. Wave number 1700cm obtained from infrared absorption spectrum -1 ~1800cm -1 The maximum absorbance (A) at 1700 cm corresponds to the absorption spectrum derived from the C=O stretching vibration of the ester group. -1 ~1800cm -1No peak separation was performed even when other absorption spectra overlapped at 1700 cm. -1 and 1800cm -1 The line connecting these points is the baseline, 1700cm -1 and 1800cm -1 The maximum absorbance between the two peaks is indicated. Also, 1600cm -1 ~1700cm -1 The maximum absorbance at (B) corresponds to the absorption spectrum derived from the alkene C=C stretching vibration. -1 ~1700cm -1 No peak separation was performed even when other absorption spectra overlapped at 1600 cm. -1 and 1700cm -1 The line connecting these points is the baseline, and the distance is 1600 cm. -1 and 1700cm -1 The maximum absorbance between the two peaks is indicated. As described above, the resin fine particles were measured by the ATR method using an infrared spectrophotometer, and the infrared spectrum was obtained at a wave number of 1700 cm -1 ~1800cm -1 Maximum peak height (maximum absorbance) (A), wavenumber 1600 cm -1 ~1700cm -1 The maximum peak height (maximum absorbance) was taken as (B), and the absorbance ratio was calculated using (Equation 1). (Formula 1) Absorbance ratio = (B) / (A)
[0071] <Moisture content> Coulometric titration method Using a trace moisture measuring device (Mitsubishi Chemical Analytech Co., Ltd., Model CA-310), coulometric titration was performed by the Karl Fischer method in accordance with JIS K0113 to measure the moisture content of the resin microparticles.
[0072] <Amount of unreacted vinyl monomer in resin particles> 5 mL of methanol is added to 0.01 g of resin microparticles, thoroughly mixed, and then allowed to stand for 24 hours to obtain a dispersion. The dispersion is then centrifuged for 30 minutes at a stirring speed of 18,500 rpm to precipitate insoluble matter. The amount of residual monomer relative to the resin microparticles is measured by analyzing 2 μL of the resulting supernatant using an ultra-high performance liquid chromatogram La Chrom Ultra (Hitachi High-Technologies Corporation). The measurement conditions were as follows: La Chrom Ultra C18 2 μm column, column temperature 40° C., solvent 0.05% trifluoroacetic acid aqueous solution and acetonitrile mixture (50 / 50 w / w), flow rate 0.6 mL / min.
[0073] <Adhesion evaluation> Two parts of resin particles were added as a binder to a mixture of 55 parts of pentaerythritol triacrylate and 38 parts of acryloylmorpholine, and then stirred and mixed. Five parts of Irgacure 184 were added as a photopolymerization initiator, and the mixture was applied to a PET film with an applicator to a film thickness of 10 μm, and then exposed to 400 mJ / cm 2 with a metal halide lamp. 2 After standing at room temperature for one week, the adhesion was evaluated using the following adhesion evaluation test. (Adhesion evaluation test) The coating was rubbed 10 times with #1000 steel wool while applying a load of 200g, and the powder on the coating was visually observed and evaluated. Those in which no detachment of resin particles was observed were rated as A, and those in which detachment of resin particles was observed were rated as D.
[0074] <Residual surfactant amount> The resin particles were extracted with a solvent and measured using a liquid chromatograph linear ion trap mass spectrometer (LC / MS / MS device). The LC / MS / MS devices used were "UHPLC ACCELA" manufactured by Thermo Fisher Scientific and "Linear Ion Trap LC / MSn LXQ" manufactured by Thermo Fisher Scientific. The surfactant content is measured by the following method. Approximately 0.01 g of resin microparticles were precisely weighed into a centrifuge tube, the extraction liquid was poured in, and the resin microparticles and the extraction liquid were thoroughly mixed. After ultrasonic extraction, the mixture was mixed again and centrifuged, and the resulting supernatant was filtered to prepare the test liquid. The concentration of the surfactant in this test solution was measured using an LC / MS / MS device, and the content was calculated from the peak area value on the obtained chromatogram using a calibration curve prepared in advance.The surfactant content in the resin microparticles was then calculated using the following formula from the measured surfactant concentration in the test solution, the weight of the resin microparticles used as a sample (sample weight), and the amount of the extracted solution. Surfactant content = surfactant concentration in test solution x volume of extract ÷ sample weight The method for creating the calibration curve is as follows. After preparing an intermediate standard solution (methanol solution) of the surfactant at approximately 1000 ppm, it was further diluted stepwise with methanol to prepare standard solutions for creating a calibration curve at 20 ppm, 10 ppm, 5 ppm, and 2.5 ppm. The standard solutions for creating a calibration curve at each concentration were measured under the following conditions, and the peak area values on the chromatogram of the monitor ion m / z = 730 to 830 were obtained. Each concentration and the area value were plotted to obtain an approximation curve (quadratic curve) by the least squares method, and this was used as the calibration curve for quantification.
[0075] <Volume average particle size, number average particle size> The volume average particle size and number average particle size of the resin microparticles were measured using a laser diffraction scattering type particle size distribution analyzer (model number "LS230", manufactured by Beckman Coulter, Inc.). Specifically, 0.1 g of the resin microparticle water dispersion (20% solid content) and 20 ml of 2 mass% anionic surfactant solution were placed in a test tube. Then, the resin microparticles were dispersed for 5 minutes using a test tube mixer (manufactured by AS ONE, "Test Tube Mixer TRIO HM-1N") and an ultrasonic cleaner (manufactured by AS ONE, "ULTRASONIC CLEANER VS-150") to obtain a dispersion. The volume average particle size and number average particle size of the resin microparticles in the dispersion were measured using a laser diffraction scattering type particle size distribution analyzer (manufactured by Beckman Coulter, Inc., "LS230") under the following measurement conditions while irradiating the dispersion with ultrasonic waves. (Measurement conditions for laser diffraction / scattering particle size distribution analyzer) medium = water Refractive index of medium = 1.333 Refractive index of solid = Refractive index of resin particles PIDS relative concentration: 40-55% The optical model used in the measurement was adjusted to the refractive index of the resin microparticles produced. When one type of monomer was used to produce the resin microparticles, the refractive index of the homopolymer of that monomer was used as the refractive index of the resin microparticles. When multiple types of monomers were used to produce the resin microparticles, the average value obtained by weighting the refractive index of the homopolymer of each monomer by the amount of each monomer used was used as the refractive index of the resin microparticles. From the measurement results, a volumetric particle size distribution of the resin fine particles was obtained, and the arithmetic mean of the volumetric particle size distribution was taken as the volumetric average particle diameter of the resin fine particles.
[0076] <Variation coefficient of volume average particle size> The coefficient of variation (CV value) of the volume average particle diameter of the resin fine particles was calculated by the following formula. Coefficient of variation of volume average particle diameter of resin microparticles = [(Standard deviation of volume-based particle size distribution of resin microparticles) / (Volume average particle diameter of resin microparticles)] x 100
[0077] [Example 1] <Production of resin particles> In a polymerization vessel equipped with a stirrer, a thermometer, and a cooling mechanism, 320 parts of ion-exchanged water and 0.2 parts of Aqualon AR-1025 (manufactured by Daiichi Kogyo Seiyaku Co., Ltd.) were mixed. In another vessel, 3.8 parts of methyl methacrylate and 0.2 parts of ethylene glycol dimethacrylate were mixed and charged into the polymerization vessel, and the mixture was stirred for 10 minutes at 8000 rpm with a TK homomixer (manufactured by Primix Corporation) to obtain a monomer mixture. After purging the polymerization vessel with nitrogen for 5 minutes, the temperature was raised to 85°C, and when the temperature reached 85°C, 0.2 parts of VA-086 (manufactured by Fujifilm Wako Pure Chemical Industries, Ltd.) dissolved in 10 parts of ion-exchanged water was charged and reacted for 1 hour to obtain a slurry (1). Next, in a separate container from the one used above, 36 parts of ion-exchanged water, 0.3 parts of Aqualon AR-1025 (manufactured by Daiichi Kogyo Seiyaku Co., Ltd.), and 0.03 parts of Aqualon AN-5065 (manufactured by Daiichi Kogyo Seiyaku Co., Ltd.) were mixed to obtain a surfactant solution. In a separate container, 36 parts of ethylene glycol dimethacrylate were thoroughly mixed and added to the surfactant solution, followed by stirring at 8000 rpm for 10 minutes with a TK homomixer (manufactured by Primix Corporation) to obtain a monomer mixture (2). The monomer mixture (2) was added in eight portions over a period of two hours to the slurry (1) maintained at 85° C. in the polymerization vessel, and then the mixture was aged for one hour, heated to 100° C. and maintained at that temperature for three hours, and then cooled to prepare a slurry containing fine resin particles. The slurry containing the fine resin particles was passed through a 400 Mesh nylon net to classify the fine resin particles, thereby obtaining a classified fine resin particle slurry. The classified resin microparticle slurry was spray-dried using a spray dryer (manufactured by Sakamoto Giken Co., Ltd., machine name: spray dryer, type: atomizer take-up type, model number: TRS-3WK) under the following equipment conditions to obtain an aggregate of resin microparticles.
[0078] <Equipment conditions> Slurry supply rate containing resin particles: 25mL / min Atomizer rotation speed: 12000 rpm Air volume: 2m 3 / min Inlet temperature (temperature of the slurry inlet containing resin fine particles, which is provided in the spray dryer and through which the slurry containing resin fine particles is sprayed and introduced): 150°C Outlet temperature (the temperature of the powder outlet from which the vinyl resin fine particles are discharged from the spray dryer): 70°C The resulting aggregate of resin particles was subjected to a crushing treatment using a current jet mill (manufactured by Nisshin Engineering, product name: CJ-10, crushing air pressure: 0.5 MPa), to obtain the target resin particles.
[0079] <Physical properties of resin particles> The volume average particle diameter of the obtained resin microparticles was 183 nm, and the coefficient of variation was 20.8%. In addition, the infrared spectrum of the obtained resin microparticles measured by the ATR method using an infrared spectrophotometer showed a wave number of 1700 cm -1 ~1800cm -1 Maximum peak height (maximum absorbance) (A) = 0.1921, wavenumber 1600 cm -1 ~1700cm -1 The maximum peak height (maximum absorbance) (B) was confirmed to be 0.00965, and the absorbance ratio (B) / (A) was 0.05023. The adhesion test result was an A. The physical properties and evaluation results of the obtained resin microparticles are shown in Table 1.
[0080] [Example 2] The resin microparticles were obtained under the same production conditions as in Example 1, except that the 36 parts of ethylene glycol dimethacrylate used in preparing the monomer mixture (2) was changed to 34 parts of ethylene glycol dimethacrylate and 2 parts of styrene. The physical properties and evaluation results of the obtained resin microparticles are shown in Table 1.
[0081] [Example 3] The resin microparticles were obtained under the same production conditions as in Example 1, except that the 36 parts of ethylene glycol dimethacrylate used in preparing the monomer mixture (2) was changed to 24 parts of ethylene glycol dimethacrylate and 12 parts of methyl methacrylate. The physical properties and evaluation results of the obtained resin microparticles are shown in Table 1.
[0082] [Example 4] In a polymerization vessel equipped with a stirrer, a thermometer, and a cooling mechanism, 70 parts of ion-exchanged water were mixed with 6 parts of magnesium pyrophosphate and 0.04 parts of sodium lauryl sulfate. In another vessel, 20 parts of ethylene glycol dimethacrylate and 0.12 parts of 2,2'-azobis(2,4-dimethylvaleronitrile) were thoroughly mixed and charged into the polymerization vessel, and the mixture was stirred for 5 minutes at 7,000 rpm with a TK homomixer (manufactured by Primix Corporation) to obtain a monomer mixture. The monomer mixture obtained was further treated with a microfluidizer at 20 MPa and charged again into the polymerization vessel. After purging the polymerization vessel with nitrogen for 5 minutes, the temperature was raised to 55°C, and the reaction was carried out for 4 hours, and then the mixture was aged for 1 hour, and then the temperature was raised to 100°C and polymerized for 3 hours. The obtained resin fine particle-containing slurry was cooled and taken out, and the particles and the supernatant were separated with a centrifuge, and only the supernatant was removed. The obtained particles were redispersed in ion-exchanged water, and the washing process of separating the particles using a centrifuge and removing the supernatant was repeated, and the washing was terminated when the conductivity of the supernatant liquid became 15 μS or less. The obtained particles were dried in a vacuum oven to obtain a dry powder. The obtained dry powder was subjected to air flow classification using a turbo classifier (manufactured by Nisshin Engineering Co., Ltd.) to obtain the desired resin microparticles. The physical properties and evaluation results of the obtained resin microparticles are shown in Table 1.
[0083] [Example 5] The resin microparticles were obtained under the same production conditions as in Example 4, except that the 20 parts of ethylene glycol dimethacrylate used in preparing the monomer mixture (2) was changed to 18 parts of ethylene glycol dimethacrylate and 2 parts of pentaerythritol tetrakisthioglycolate. The physical properties and evaluation results of the obtained resin microparticles are shown in Table 1.
[0084] [Comparative Example 1] The resin microparticles were obtained under the same production conditions as in Example 1, except that the 36 parts of ethylene glycol dimethacrylate used in preparing the monomer mixture (2) was changed to 8 parts of ethylene glycol dimethacrylate and 28 parts of methyl methacrylate. The physical properties and evaluation results of the obtained resin microparticles are shown in Table 1.
[0085] [Comparative Example 2] The resin microparticles were obtained under the same production conditions as in Example 4, except that the 20 parts of ethylene glycol dimethacrylate used in preparing the monomer mixture (2) was changed to 4 parts of ethylene glycol dimethacrylate and 16 parts of methyl methacrylate. The physical properties and evaluation results of the obtained resin microparticles are shown in Table 1.
[0086] For Examples 1 to 5 and Comparative Examples 1 and 2, the volume average particle diameter, coefficient of variation, maximum absorbance (A), maximum absorbance (B), absorbance ratio (B) / (A), water content, total amount of unreacted vinyl monomer, amount of residual surfactant, and adhesion test results of the obtained resin microparticles are shown in Table 1.
[0087] [Table 1]
[0088] The present invention can be embodied in various other forms without departing from its spirit or main characteristics. Therefore, the above-described embodiments are merely illustrative in all respects and should not be interpreted as being limiting. The scope of the present invention is defined by the claims and is not limited to the text of the specification. Furthermore, all modifications and changes within the scope of the claims are within the scope of the present invention.
Claims
1. Resin microparticles obtained by polymerizing one or more vinyl monomers, In the infrared spectrum measured by the ATR method using an infrared spectrophotometer, the wave number was 1700 cm -1 ~1800cm -1 Maximum peak height (maximum absorbance) (A) and wave number 1600 cm -1 ~1700cm -1 the absorbance ratio (B) / (A) with respect to the maximum peak height (maximum absorbance) (B) is in the range of 0.020 to 0.060, The following requirements (a) to (c): (a) the amount of unreacted vinyl monomer in the resin fine particles is 1.0% by mass or less; (b) the amount of the residual surfactant relative to 100 parts by mass of the resin fine particles is 0.01 parts by mass or more and 1 part by mass or less; (c) the content of the polyfunctional vinyl monomer is in the range of 70 parts by mass to 100 parts by mass per 100 parts by mass of the vinyl monomer; It satisfies one or more of the following: Resin fine particles.
2. The resin fine particles according to claim 1 , wherein the vinyl monomer comprises a (meth)acrylic acid ester monomer.
3. 3. The resin fine particles according to claim 1, wherein the resin fine particles are a dry powder having a moisture content of 2.0% by mass or less.
4. A resin fine particle-containing composition comprising the resin fine particles according to any one of claims 1 to 3, a photopolymerization initiator and an ultraviolet-curable resin.
Citation Information
Patent Citations
MOS-type semiconductor delay device
JP1975011731A
Signal transmission equipment
JP1987058740A
Polymer fine particle, method for producing the same, and conductive fine particle and anisotropic conductive material
JP2010195992A
Porous resin particle, method for producing the porous resin particle, and use thereof
JP2013227535A
Optical film and method of manufacturing the same
JP2017181990A